Electoral violence in Nigeria : a case study of the 2011 general election in Azare Katagum local government, Nigeria - Gadau, Yau Idris (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This thesis examines the impact of electoral fraud, ethnic politics, and poverty on electoral violence in Nigeria. The analysis in this case study focuses on electoral violence in Azare Katagum Local Government with specific reference to the 2011 general election. The findings of the study indicate that there are various factors that contribute to electoral violence in Nigeria. These include among others corruption, electoral fraud, poverty and mismanagement. The study examines how political manipulation of ethno-religious divisions among the major ethnic groups in Nigeria has led to widespread electoral violence in the country. The analysis is conducted at two levels. First, the thesis examines the wider structural problems that contribute to the electoral violence at the macro level. Second, using the specific case study of electoral violence in Azare Katagum constituency during the 2011 Nigerian general elections, the thesis examines the direct causes and wider impact of such violence. Data analysis in the study employs both quantitative and qualitative methods. A questionnaire consisting of 30 questions and using a 5-point Likert scale was employed. In addition, structured interviews were conducted to complement the survey. The findings of this research highlight several additional factors that contribute to electoral violence in the area of study. These include manipulation of societal cleavages such as canvassing for votes on religious and ethnic platforms, ethnic grievances, religious intolerance among party supporters, and politics of sectionalism, identity and religious differences. Significantly, it was noted that irregularities perpetuated by INEC officials and widespread corruption in the electoral system contribute significantly to electoral violence in the country.